(untitled) (Eurasian Journal of Ecology, 2024)
This article presents a summary of the flora and the results of the floristic analysis of plants growing on the territory of the «Kokshetau» state national natural park of the «Ormandy bulak» branch. During the study, the following signs of vegetation were identified: habitat in the study area; classification of life forms by K. Raunkier and I.G. Serebryakov; ecological group in relation to moisture; economic significance. A taxonomic analysis was also carried out and the ratio of genera and species was determined. The flora of the «Ormandy bulak» branch of the «Kokshetau» SNNP has 56 species, 54 genera and 27 families. The leading genera include Rosaceae Juss., Asteraceae Dumort, Ranunculaceae Juss., Fabaceae Lindl. and Plantaginaceae Juss. Rubus L. and Galium L. they are the dominant genera. In addition, species listed in the Red Book of Kazakhstan have been identified, these are Pulsatilla patens (L.) Mill. and Adonis vernalis L. In order to preserve the full biological diversity, and not only endangered species, it is necessary to assess the current state of regional flora and vegetation diversity, assess their structure and prospects for rational use. Keywords: flora, flora synopsis, branch of «Ormandy bulak», «Kokshetau» SNNP, biodiversity, taxonomic analysis.